Specialty Dentistry for the God’s Forgotten Child - Kohli, Anil; Sahani, Surbhi; Gupta, Kritija (Journal of Orofacial Research, 2014)
Hemophilia constitute an assemblage of hereditary disorders caused due to the deficiency of one or more clotting factors leading to sustained clotting time and excessive bleeding tendency that may be ill-fated. Anticipation of bleeding during dental regimen by both patient and dental surgeon has been the elementary logic for curtailment of dutiful dental care for hemophiliacs. The apparent complexities in diagnosis and handling of a bleeding dilemma drives us to bypass such patients in clinical practice. This article presents a systematic approach to successful endodontic management in a patient with severe hemophilia A.